Determinant roles of dendritic cell-expressed Notch Delta-like and Jagged ligands on anti-tumor T cell immunity. Issue 1 (2nd April 2019) - Tchekneva, Elena E.; Goruganthu, Mounika U.L.; Uzhachenko, Roman V.; Thomas, Portia L.; Antonucci, Anneliese; Chekneva, Irina; Koenig, Michael; Piao, Longzhu; Akhter, Anwari; de Aquino, Maria Teresa P.; Ranganathan, Parvathi; Long, Nicholas; et al.
Abstract : Background: Notch intercellular communication instructs tissue-specific T-cell development and function. In this study, we explored the roles of dendritic cell (DC)-expressed Notch ligands in the regulation of T-cell effector function. Methods: We generated mice with CD11c lineage-specific deletion of Notch Delta-like ligand (Dll)1 and Jagged (Jag)2. Using these genetically-ablated mice and engineered pharmacological Notch ligand constructs, the roles of various Delta-like and Jagged ligands in the regulation of T-cell-mediated immunity were investigated. We assessed tumor growth, mouse survival, cytokine production, immunophenotyping of myeloid and lymphoid populations infiltrating the tumors, expression of checkpoint molecules and T-cell function in the experimental settings of murine lung and pancreatic tumors and cardiac allograft rejection. Correlative studies were also performed for the expression of NOTCH ligands, NOTCH receptors and PD-1 on various subsets of myeloid and lymphoid cells in tumor-infiltrating immune cells analyzed from primary human lung cancers. Results: Mice with CD11c lineage-specific deletion of Notch ligand gene  Dll1, but not Jag2, exhibited accelerated growth of lung and pancreatic tumors concomitant with decreased antigen-specific CD8 + T-cell functions and effector-memory (Tem) differentiation. Increased IL-4 but decreased IFN-γ production and elevated populations of T-regulatory and myeloid-derived suppressor cells were observed in Dll1 -ablated mice. Multivalent clustered DLL1-triggered Notch signaling overcame DC Dll1 deficiency and improved anti-tumor T-cell responses, whereas the pharmacological interference by monomeric soluble DLL1 construct suppressed the rejection of mouse tumors and cardiac allograft. Moreover, monomeric soluble JAG1 treatment reduced T-regulatory cells and improved anti-tumor immune responses by decreasing the expression of PD-1 on CD8 + Tem cells. A significant correlation was observed between DC-expressed Jagged and Delta-like ligands with Tem-expressed PD-1 and Notch receptors, respectively, in human lung tumor-infiltrates. Conclusion: Our data show the importance of specific expression of Notch ligands on DCs in the regulation of T-cell effector function. Thus, strategies incorporating selectively engineered Notch ligands could provide a novel approach of therapeutics for modulating immunity in various immunosuppressive conditions including cancer.